Development of Hill Cipher Method For Encryption And Decryption of Drug Prescriptions to Improve Data Security - Ardhani, Rahmad; Hermawati, Hermawati; Munir, Muhammad Misbahul (Sistemasi: Jurnal Sistem Informasi, 2024)
A prescription is a written request from a doctor to a pharmacist, as not everyone can know the dosage or type of a particular drug, especially patients who need a prescription for the drug must be kept secret. Rapid technological advances can have an impact on all sectors, both private and government, including the medical field. One of the medical services that utilizes IT is to send prescription messages electronically to pharmacists in response to doctors' requests. The many misuse of prescription drugs by irresponsible people and misreading prescription drugs by pharmacists can be fatal for patients, so a solution is needed to overcome these problems. The purpose of this study is to create an encrypted electronic recipe application using the Hill Cipher method. This research method generally starts from data collection, data analysis and encryption model development. Applications designed with the Hill Cipher Algorithm are developed with modified algorithm keys using postal code patterns as the matrix keys, this aims to achieve the maximum level of security. The results of the system functionality test using the black box method obtained normal results for all system test scenarios. Validity testing yields valid results. The final test, through questionnaire testing, obtained a good level of system feasibility, namely an average level of Service of 83%, Features of 78% and Performance of 81%. Overall, the system has given a good performance score as the accuracy of the system is above 70%.